A high-purity silicon carbide / titanium silicon carbon composite material product and preparation method thereof
Silicon carbide/titanium-silicon carbon composite materials were prepared by the silicon-titanium alloy seepage method, which reduced the content of the melt-silicon alloy, improved the density, bending strength and fracture toughness of the material, and solved the low toughness and high temperature resistance of the reactive sintered silicon carbide materials. Problem of insufficient corrosiveness.
Patent Information
- Application Number
- CN202311241877.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-25
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-09-25
AI Technical Summary
The problems of low toughness, high temperature resistance and corrosion resistance of reactive sintered silicon carbide materials are mainly due to the high content of residual silicon and melted metals, which lead to a decrease in mechanical properties and heat resistance.
By using silicon titanium alloy to melt the silicon carbide green body, coordinate the alloy composition, porosity and carbon addition amount of the green body, a high-purity silicon carbide/titanium silicon silicon carbon composite material is prepared to reduce the melting alloy in the product content, improve the mechanical properties of the material and heat and corrosion resistance.
The prepared silicon carbide/titanium-silicon carbon composite has high density, significantly improved flexural strength at room temperature and high temperature, and significantly improved fracture toughness, which solved the decline in mechanical properties and insufficient corrosion resistance of the original materials at high temperatures. question.
Smart Images

Figure HDA0004467600330000011 
Figure HDA0004467600330000012 
Figure HDA0004467600330000013
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic composite material sintering, and specifically relates to a high-purity silicon carbide / titanium silicon carbon composite material product and a preparation method thereof. Background Art
[0002] Silicon carbide (SiC) ceramics have high strength, high elastic modulus and high heat and corrosion resistance, and can play an important role in high temperature and extreme environments. At present, the methods used to prepare silicon carbide mainly include recrystallization, reaction sintering, liquid phase sintering, spark plasma sintering, hot pressing and hot isostatic pressing sintering. Among these preparation methods, reaction sintering has the advantages of low sintering temperature, easy size control, and no need for sintering aids. Therefore, it is a very important silicon carbide preparation process. However, the typical production process of reaction sintered silicon carbide includes infiltrating molten silicon into a green porous silicon carbide / carbon green body to obtain a composite material composed of silicon carbide and residual silicon. Due to the high brittleness, low melting point and easy corrosion of residual silicon, the performance of reaction sintered silicon carbide is significantly affected. In order to improve the performance of reaction sintered silicon carbide composites, the introduction of titanium silicon carbon (Ti3SiC2) with excellent fracture toughness, good thermal shock resistance and good machinability is a worthy idea to improve the mechanical properties, high temperature resistance and corrosion resistance of reaction sintered silicon carbide. The difficulty in preparing silicon carbide / titanium silicon carbon composites by reactive infiltration is how to reduce the content of the infiltration phase. Too high a content of infiltration metal will affect the mechanical properties, high temperature resistance and corrosion resistance of the composite material. Summary of the invention
[0003] In order to solve the problems existing in the prior art, the present invention provides a high-purity silicon carbide / titanium silicon-carbon composite material product and a preparation method thereof, wherein a silicon-titanium alloy is used to infiltrate a silicon carbide / carbon green body, and the content of the infiltrated alloy in the finished product is minimized by synergistically adjusting the alloy composition, the porosity of the green body and the amount of carbon added, thereby preparing a silicon carbide / titanium silicon-carbon composite material containing different contents of SiC and Ti3SiC2, thereby solving the problems of low toughness, high temperature resistance and corrosion resistance of existing reaction-sintered silicon carbide materials.
[0004] In order to achieve the above object, the technical solution adopted by the present invention is: a method for preparing a high-purity silicon carbide / titanium silicon-carbon composite material product, which specifically comprises the following steps:
[0005] A green body is prepared by using a carbon source and silicon carbide powder, wherein the green body has a porosity of 25% to 55%; the mass fraction of the carbon source in the green body is 10wt.% to 90wt.%, and the rest is silicon carbide powder;
[0006] The green body is placed on the flat silicon-titanium alloy powder, and heated under vacuum conditions until the silicon-titanium alloy powder melts into liquid and penetrates into the green body, so that the carbon reacts with the silicon-titanium alloy to obtain a silicon carbide / titanium silicon-carbon product;
[0007] The obtained silicon carbide / titanium silicon carbon product is subjected to high temperature heat treatment to allow the residual silicon-titanium alloy and carbon to fully react, and the silicon carbide / titanium silicon carbon product after high temperature heat treatment is polished to obtain a high-purity silicon carbide / titanium silicon carbon composite material product.
[0008] The method of preparing a green body using a carbon source and silicon carbide powder includes:
[0009] The carbon source and silicon carbide powder are wet mixed and ball milled, and then dried and sieved through a 150-mesh sieve, and the sieved powder is added with phenolic resin or PVA to obtain a wet mixture, and the wet mixture is dried and then dry mixed to obtain a uniformly mixed carbon source and silicon carbide powder;
[0010] Forming the green body using compression molding, gel casting or extrusion;
[0011] When using the molding method, the carbon source, silicon carbide powder and binder are mixed evenly, and then molded to obtain a green body;
[0012] Alternatively, when using gel casting molding, a uniformly mixed carbon source is mixed with silicon carbide powder, a dispersant binder and water to prepare a ceramic slurry, the slurry is poured into a porous gypsum mold, and the ceramic slurry is solidified into a gel state by reacting with acrylamide or agarose, and the gel is taken out and dried to remove excess water and shrinkage to obtain a green body;
[0013] Alternatively, when the extrusion method is used for molding, the uniformly mixed raw materials are molded, a set amount of water is added to the powder, and a green body is molded by extrusion molding to obtain a green body.
[0014] The particle size of the silicon carbide powder used is in the range of 0.5 to 50 μm, and the crystal form is 6H or 3C; the carbon source is nano carbon black, mesophase carbon microspheres, artificial graphite, natural graphite, diamond, activated carbon or petroleum coke, and the specifications used are as follows:
[0015] The particle size of nano carbon black is less than 500nm; the particle size of mesophase carbon microspheres is 2-20μm; the particle size of artificial graphite is 2-20μm; the particle size of natural graphite is 2-20μm; the particle size of diamond is 0.2-50μm; and the particle size of petroleum coke is 2-70μm.
[0016] A planetary ball mill is used for wet mixing, the speed of the planetary ball mill is 180r / min~200r / min, and the powder is mixed for 4 hours. A planetary ball mill is used for dry mixing, the speed of the planetary ball mill is 100r / min~120r / min, and the powder is mixed for 5 hours.
[0017] When preparing green bodies with carbon sources and silicon carbide powder, different molding methods are selected according to the use requirements of different workpieces: for structural parts, compression molding or isostatic pressing is used; for porous parts, grouting molding is used; for pipes, injection molding or extrusion molding is used.
[0018] The green body is placed on the flat silicon-titanium alloy powder and heated under vacuum conditions until the silicon-titanium alloy powder melts into liquid and penetrates into the green body, so that the carbon reacts with the silicon-titanium alloy to obtain a silicon carbide / titanium silicon-carbon product. The heating temperature is 1600°C to 1700°C, the holding time is 30 to 180 minutes, and the vacuum degree is not greater than 50Pa.
[0019] The composition range of silicon-titanium alloy powder is 37Ti63Si~50Ti50Si, and the particle size is 0.2-5mm.
[0020] The heat treatment temperature of the obtained silicon carbide / titanium silicon carbon product is 1600°C to 1800°C, the insulation time is 2h, and the vacuum degree is 20Pa.
[0021] The silicon carbide / titanium silicon carbon composite material products after high temperature heat treatment are polished to remove the condensed carbon silicon on the surface and smooth the rough surface, as follows:
[0022] For products with low requirements for surface finish, sandblasting is used, and the sandblasting pressure is 0.6MPa;
[0023] For products with high requirements for surface finish, sandblasting is first performed with a sandblasting pressure of 0.6MPa, and then polishing is performed. The abrasive particle sizes are 7μm, 5μm, 3.5μm, 1.5μm and 1μm respectively.
[0024] The present invention can also provide a high-purity silicon carbide / titanium silicon-carbon composite material product, which is obtained by the above-mentioned preparation method of the high-purity silicon carbide / titanium silicon-carbon composite material product. The obtained silicon carbide / titanium silicon-carbon composite material product has a density of 3.46 g / cm 3 ~3.90g / cm 3 The volume fraction of residual silicon-titanium alloy in the obtained silicon carbide product is not more than 5 vol.%, the content of Ti3SiC2 in the obtained silicon carbide / titanium silicon-carbon composite material is 15 vol.%-58 vol.%, and the rest is SiC phase; the obtained silicon carbide / titanium silicon-carbon composite material product has a flexural strength of 450MPa-580MPa at room temperature, a flexural strength of 320MPa-370MPa at 1000°C, and a fracture toughness of 4.6-6.5MPa·m 1 / 2 .
[0025] Compared with the prior art, the present invention has at least the following beneficial effects:
[0026] The method for preparing high-purity silicon carbide / titanium silicon carbon composite materials by a two-step reaction sintering method of the present invention solves the problems of the existing reaction sintered silicon carbide materials, such as the decrease in high-temperature mechanical properties, decrease in elastic modulus, and decrease in corrosion resistance due to the presence of sintering aids and residual silicon. The method for preparing high-purity silicon carbide / titanium silicon carbon composite materials by a reaction sintering method of the present invention reduces the content of the infiltration alloy as much as possible by synergistically adjusting the composition of the infiltration alloy, the porosity of the green body, and the amount of carbon added, and prepares a silicon carbide / titanium silicon carbon composite material that can prepare high-purity and dense silicon carbide materials. The density of the obtained silicon carbide / titanium silicon carbon composite material product is 3.0g / cm 3 ~4.10g / cm 3 The volume fraction of residual silicon-titanium alloy in the obtained silicon carbide product is not more than 5vol.%. The content of Ti3SiC2 in the obtained silicon carbide / titanium silicon-carbon composite material is 15vol.%-58vol.%, and the rest is SiC phase. The obtained silicon carbide / titanium silicon-carbon composite material product has a flexural strength of 250MPa-700MPa at room temperature, a flexural strength of 200MPa-500MPa at 1000℃-1400℃, and a fracture toughness of 2.5-7.6MPa·m 1 / 2 . BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the backscattered image of the microstructure of 75SiC-25Ti3SiC2 composite material.
[0028] Figure 2 This is the XRD pattern of 75SiC-25Ti3SiC2 composite material.
[0029] Figure 3 This is the toughening mechanism of 75SiC-25Ti3SiC2 composite materials. DETAILED DESCRIPTION
[0030] The present invention is described in detail below in conjunction with specific implementation modes.
[0031] Example 1
[0032] This embodiment adopts a two-step reaction sintering method to prepare a 80SiC-20Ti3SiC2 composite material product, which specifically includes the following steps:
[0033] In the first step, 12wt% nano carbon black and 88wt% 6H silicon carbide powder were mixed, and 5wt% phenolic resin was added as a binder; wet mixing was first performed at a speed of 180r / min for 4h, and then dry mixing was performed at a speed of 100r / min for 5h;
[0034] The second step is to press the dried mixed powder into a mold by a compression molding method, fill the powder evenly into the mold, apply unidirectional pressure of 60 MPa, and hold the pressure for 60 seconds; the porosity of the green body is controlled to 20%.
[0035] The third step is to place the green body molded in the second step on the flat silicon-titanium alloy powder, and put the silicon-titanium alloy powder with a composition of 50Ti50Si into a vacuum furnace for sintering. The heating rate is 5°C / min, and the temperature is increased to 1650°C, and the temperature is kept for 30 minutes; the vacuum degree is 10Pa;
[0036] The fourth step is to heat treat the silicon carbide / titanium silicon carbon composite material product obtained in the third step at a heat treatment temperature of 1700° C., for 2 hours, and at a vacuum degree of 20 Pa;
[0037] In the fifth step, the silicon carbide / titanium silicon carbon composite material product obtained in the fourth step is polished, and the residual silicon on the surface of the sample is treated by sand blasting, and the sand blasting pressure is 0.6 MPa.
[0038] The density of the silicon carbide / titanium silicon carbon composite material in this embodiment is 3.46 g / cm 3 The obtained silicon carbide product has a flexural strength of 520MPa at room temperature, a flexural strength of 350MPa at 1000℃, and a fracture toughness of 4.6MPa·m 1 / 2 .
[0039] Example 2
[0040] This embodiment adopts a reaction sintering method to prepare a 70SiC-30Ti3SiC2 composite material product, which specifically includes the following steps:
[0041] In the first step, 10wt.% of petroleum coke, 13wt.% of nano carbon black and 77wt.% of silicon carbide powder were mixed, and 2wt.% of cellulose was added as a dispersant; a planetary ball mill was used for wet mixing for 4 hours at a speed of 200r / min, and after drying, a planetary ball mill was used for dry mixing for 3 hours at a speed of 120r / min;
[0042] The second step is to shape the mixed raw materials, add 0.2 times the weight of the powder into water, and use extrusion molding to shape the green body. The length of the shaping section is 28mm, the extrusion angle is 45°, and the maximum radial speed is 1.5μm / s. The green body after molding is dried at 70℃ for 72h to ensure that the porosity of the green body is 31%;
[0043] The third step is to place the green body prepared in the second step on the flat silicon-titanium alloy powder, and use the silicon-titanium alloy powder with a composition of 50Ti50Si, put it into a vacuum furnace for sintering, and heat it up to 1650°C at a rate of 5°C / min, and keep it warm for 30 minutes; the vacuum degree is 40Pa;
[0044] Step 4: heat-treating the silicon carbide / titanium silicon carbon composite material obtained in the step 3 at a temperature of 1720°C for 2 hours and a vacuum degree of 20 Pa;
[0045] In the fifth step, the silicon carbide / titanium silicon carbon composite material product obtained in the fourth step is polished, and the residual silicon on the surface of the sample is treated by sand blasting, and the sand blasting pressure is 0.6 MPa.
[0046] The density of the silicon carbide / titanium silicon carbon composite material in this embodiment is 3.7 g / cm 3 The obtained silicon carbide / titanium silicon carbon composite material has a flexural strength of 500MPa at room temperature, a flexural strength of 350MPa at 1000℃, and a fracture toughness of 5.8MPa·m 1 / 2 .
[0047] Example 3
[0048] This embodiment adopts a reaction sintering method to prepare a 60SiC-40Ti3SiC2 composite material product, which specifically includes the following steps:
[0049] In the first step, 25wt.% of petroleum coke, 20wt.% of nano carbon black and 55wt.% of 6H silicon carbide powder were mixed respectively; the mixture was wet-mixed for 4h using a planetary ball mill at a speed of 200r / min, and after drying, the mixture was dry-mixed for 3h using a planetary ball mill at a speed of 120r / min;
[0050] In the second step, ceramic slurry is prepared by mixing ceramic powder with a dispersant binder and water, the slurry is poured into a mold made of porous gypsum, the slurry is solidified into a gel by reacting with acrylamide or agarose, the gel is removed from the mold and dried to remove excess moisture and shrinkage, and the green body porosity is ensured to be 43%;
[0051] The third step is to place the green body prepared in the second step on the flat silicon-titanium alloy powder, and use the silicon-titanium alloy powder with a composition of 50Ti50Si, put it into a vacuum furnace for sintering, and heat it up to 1700°C at a rate of 5°C / min, and keep it warm for 30min; the vacuum degree is 30Pa;
[0052] The fourth step is to heat treat the silicon carbide / titanium silicon carbon composite material obtained in the third step at a heat treatment temperature of 1800°C, for 2 hours, and at a vacuum degree of 20 Pa;
[0053] In the fifth step, the silicon carbide / titanium silicon carbon composite material product obtained in the fourth step is polished, and the residual silicon on the surface of the sample is treated by sand blasting, and the sand blasting pressure is 0.6 MPa.
[0054] The density of the silicon carbide / titanium silicon carbon composite material in this embodiment is 3.52 g / cm 3 The volume fraction of residual silicon-titanium alloy in the obtained silicon carbide / titanium silicon-carbon composite material product is 1 vol.%, the porosity is less than 1 vol.%, and the flexural strength of the obtained silicon carbide / titanium silicon-carbon composite material is 450 MPa at room temperature, 350 MPa at 1000 ° C, and the fracture toughness is 6.5 MPa·m 1 / 2 .
[0055] Example 4
[0056] This embodiment adopts a reaction sintering method to prepare a 65SiC-35Ti3SiC2 composite material product, which specifically includes the following steps:
[0057] In the first step, 25wt.% of petroleum coke, 10wt.% of nano carbon black and 65wt.% of 3C silicon carbide powder were mixed, and 5wt.% of phenolic resin was added as a binder; a planetary ball mill was used for wet mixing for 4 hours at a speed of 200r / min, and after drying, a planetary ball mill was used for dry mixing for 3 hours at a speed of 120r / min;
[0058] The second step is to shape the mixed raw materials, add 0.2 times the weight of the powder into water, and use extrusion molding to shape the green body. The length of the shaping section is 28mm, the extrusion angle is 45°, and the maximum radial speed is 1.5μm / s. The green body after shaping is dried at 70℃ for 72h to ensure that the porosity of the green body is 36%;
[0059] The third step is to place the green body prepared in the second step on the flat silicon-titanium alloy powder, and use the silicon-titanium alloy powder with a composition of 50Ti50Si, put it into a vacuum furnace for sintering, and heat it up to 1650°C at a rate of 5°C / min, and keep it warm for 30 minutes; the vacuum degree is 50Pa;
[0060] Step 4: heat-treating the silicon carbide / titanium silicon carbon composite material obtained in the step 3 at a temperature of 1720°C for 2 hours and a vacuum degree of 20 Pa;
[0061] In the fifth step, the silicon carbide / titanium silicon carbon composite material product obtained in the fourth step is polished, and the residual silicon on the surface of the sample is treated by sand blasting, and the sand blasting pressure is 0.6 MPa.
[0062] The density of the silicon carbide / titanium silicon carbon composite material in this embodiment is 3.62 g / cm 3The obtained silicon carbide / titanium silicon carbon composite material has a flexural strength of 525MPa at room temperature, a flexural strength of 360MPa at 1000℃, and a fracture toughness of 6.1MPa·m 1 / 2 .
[0063] Example 5
[0064] This embodiment adopts a two-step reaction sintering method to prepare a 75SiC-25Ti3SiC2 composite material, which specifically includes the following steps:
[0065] In the first step, 20wt.% nano carbon black and 80wt.% 6H silicon carbide powder were mixed, and 5wt.% phenolic resin was added as a binder; wet mixing was first performed at a speed of 180r / min for 4h, and then dry mixing was performed at a speed of 100r / min for 5h;
[0066] The second step is to press the powder into shape by a compression molding method, fill the powder into the mold evenly, apply bidirectional pressure at a pressure of 60 MPa, and hold the pressure for 60 seconds; the porosity of the green body is controlled to 28%.
[0067] The third step is to place the green body molded in the second step on the flat silicon-titanium alloy powder, and use the silicon-titanium alloy powder with a composition of 50Ti50Si, put it into a vacuum furnace for sintering, and heat it up to 1600°C at a rate of 5°C / min, and keep it warm for 30 minutes; the vacuum degree is 40Pa;
[0068] The fourth step is to heat treat the silicon carbide / titanium silicon carbon composite material product obtained in the third step at a heat treatment temperature of 1700° C., for 2 hours, and at a vacuum degree of 20 Pa;
[0069] In the fifth step, the silicon carbide / titanium silicon carbon composite material product obtained in the fourth step is polished, and the residual silicon on the surface of the sample is treated by sand blasting, and the sand blasting pressure is 0.6 MPa.
[0070] The density of the silicon carbide / titanium silicon carbon composite material in this embodiment is 3.5 g / cm 3 The obtained silicon carbide product has a flexural strength of 523MPa at room temperature, a flexural strength of 370MPa at 1000℃, and a fracture toughness of 4.8MPa·m 1 / 2 ; The backscattered image of the microstructure of the silicon carbide / titanium silicon carbon composite material prepared in this embodiment is referenced Figure 1 、XRD spectrum reference Figure 2 , toughening mechanism reference Figure 3As can be seen from the figure, the fracture surface of the sample shows uneven characteristics, with many steps and cleavage planes. This shows that the sample has undergone a complex fracture process during loading, forming a variety of fracture morphologies, mainly intragranular fracture. At the same time, part of the fracture surface of the TiSi2 phase is relatively flat, showing the phenomenon of transverse intragranular fracture. This may be due to the low fracture toughness of the TiSi2 phase, which leads to a relatively flat fracture surface when it breaks. The extended Ti3SiC2 grains have unique lamellar characteristics, making them easy to identify in the sample. At the same time, the Ti3SiC2 grains with intragranular fracture also show lamellar characteristics, and many peeled and pulled grains can be observed on the fracture surface, which shows that the sample has high toughness. In addition, the Ti3SiC2 grains show a deflected morphology during the fracture process, which can be attributed to the lattice deformation caused by crack extension. In order to simulate and analyze the crack propagation behavior of the composite material, the study used a tetrahedral diamond indenter to introduce cracks on the surface of the polished sample. Figure 3 (bd) show the morphology of crack propagation in the specimen. Figure 3 (b) The distribution of microcracks in the TiSi2 phase can promote the bifurcation of the main crack during propagation. As a result, the crack path becomes more tortuous, leading to an increase in surface energy, hindering crack propagation, and thus improving the toughness of the composite material. In addition, Figure 3 (c) shows the phenomenon of Ti3SiC2 grains being pulled out from the TiSi2 phase interface during crack propagation, highlighting the unique behavior of this material. Figure 3 (d) shows the debonding phenomenon of Ti3SiC2 when the crack propagates parallel to the basal plane, and the crack propagates along the basal plane. However, when the basal plane propagates perpendicular to the crack, the crack penetrates the grain and deflects within the grain. The content of Ti3SiC2 phase is closely related to the fracture toughness of the composite material. The increase in the content of Ti3SiC2 phase leads to an increase in the fracture toughness of the material. This is because the Ti3SiC2 phase has a layered structure and high toughness, which can exert crack resistance during crack propagation. In addition, the increase in the content of Ti3SiC2 phase can also promote a series of mechanisms such as crack deflection, microcrack toughening, pull-out and crack bridging, thereby improving the fracture toughness of the composite material.
[0071] Example 6
[0072] This embodiment adopts a reaction sintering method to prepare a 68SiC-32Ti3SiC2 composite material product, which specifically includes the following steps:
[0073] In the first step, 27wt.% of nano carbon black and 73wt.% of 6H silicon carbide powder were mixed respectively; the mixture was wet-mixed for 4h using a planetary ball mill at a speed of 200r / min, and after drying, the mixture was dry-mixed for 3h using a planetary ball mill at a speed of 120r / min;
[0074] The second step is to prepare a ceramic slurry by mixing ceramic powder with a dispersant binder and water, pour the slurry into a mold made of porous gypsum, solidify the slurry into a gel by reacting with acrylamide or agarose, remove the gel from the mold and dry it to remove excess moisture and shrinkage, and ensure that the green body has a porosity of 34%;
[0075] The third step is to place the green body prepared in the second step on the flat silicon-titanium alloy powder, and use the silicon-titanium alloy powder with a composition of 50Ti50Si, put it into a vacuum furnace for sintering, and heat it up to 1700°C at a rate of 5°C / min, and keep it warm for 30 minutes; the vacuum degree is 50Pa;
[0076] The fourth step is to heat treat the silicon carbide / titanium silicon carbon composite material obtained in the third step at a heat treatment temperature of 1750°C, for 2 hours, and at a vacuum degree of 20Pa;
[0077] In the fifth step, the silicon carbide / titanium silicon carbon composite material product obtained in the fourth step is polished, and the residual silicon on the surface of the sample is treated by sand blasting, and the sand blasting pressure is 0.6 MPa.
[0078] The density of the silicon carbide / titanium silicon carbon composite material in this embodiment is 3.51 g / cm 3 The obtained silicon carbide / titanium silicon carbon composite material has a flexural strength of 450MPa at room temperature, a flexural strength of 350MPa at 1000℃, and a fracture toughness of 6.5MPa·m 1 / 2 .
[0079] Example 7
[0080] This embodiment adopts a two-step reaction sintering method to prepare a 55SiC-45Ti3SiC2 composite material product, which specifically includes the following steps:
[0081] In the first step, 70wt.% nano carbon black and 30wt.% 6H silicon carbide powder were mixed, and 5wt.% phenolic resin was added; wet mixing was first performed at a speed of 180r / min for 4h, and then dry mixing was performed at a speed of 100r / min for 5h;
[0082] The second step is to press the powder into shape by a compression molding method, fill the powder into the mold evenly, apply bidirectional pressure at a pressure of 60 MPa, and hold the pressure for 60 seconds; the porosity of the green body is controlled to be 50%.
[0083] The third step is to place the green body molded in the second step on the flat silicon-titanium alloy powder, and use the silicon-titanium alloy powder with a composition of 50Ti50Si, put it into a vacuum furnace for sintering, and heat it up to 1650℃ at a rate of 5℃ / min, and keep it warm for 30min; the vacuum degree is 40pa;
[0084] The fourth step is to heat treat the silicon carbide / titanium silicon carbon composite material product obtained in the third step at a heat treatment temperature of 1700° C., for 2 hours, and at a vacuum degree of 20 Pa.
[0085] In the fifth step, the silicon carbide / titanium silicon carbon composite material product obtained in the fourth step is polished, and the residual silicon on the surface of the sample is treated by sand blasting, and the sand blasting pressure is 0.6 MPa.
[0086] The density of the silicon carbide / titanium silicon carbon composite material in this embodiment is 3.67 g / cm 3 The obtained silicon carbide product has a flexural strength of 550MPa at room temperature, a flexural strength of 350MPa at 1000℃, and a fracture toughness of 5.6MPa·m 1 / 2 .
[0087] Example 8
[0088] This embodiment adopts a two-step reaction sintering method to prepare a 50SiC-50Ti3SiC2 composite material product, which specifically includes the following steps:
[0089] In the first step, 90wt.% nano carbon black and 10wt.% 3C silicon carbide powder were mixed, and 5wt.% phenolic resin was added; wet mixing was first performed at a speed of 180r / min for 4h, and then dry mixing was performed at a speed of 100r / min for 5h;
[0090] The second step is to press the powder into shape by a compression molding method, fill the powder into the mold evenly, apply bidirectional pressure at a pressure of 60 MPa, and hold the pressure for 60 seconds; the porosity of the green body is controlled to be 55%.
[0091] The third step is to place the green body molded in the second step on the flat silicon-titanium alloy powder, and use the silicon-titanium alloy powder with a composition of 50Ti50Si, put it into a vacuum furnace for sintering, and heat it up to 1650℃ at a rate of 5℃ / min, and keep it warm for 60min; the vacuum degree is 40pa;
[0092] The fourth step is to heat treat the silicon carbide / titanium silicon carbon composite material product obtained in the third step at a heat treatment temperature of 1700° C., for 2 hours, and at a vacuum degree of 20 Pa.
[0093] In the fifth step, the silicon carbide / titanium silicon carbon composite material product obtained in the fourth step is polished, and the residual silicon on the surface of the sample is treated by sand blasting, and the sand blasting pressure is 0.6 MPa.
[0094] The density of the silicon carbide / titanium silicon carbon composite material in this embodiment is 3.71 g / cm 3 The obtained silicon carbide product has a flexural strength of 550MPa at room temperature, a flexural strength of 350MPa at 1000℃, and a fracture toughness of 5.3MPa·m 1 / 2 .
[0095] Example 9
[0096] This embodiment adopts a two-step reaction sintering method to prepare a 62SiC-38Ti3SiC2 composite material, which specifically includes the following steps:
[0097] In the first step, 60wt.% nano carbon black and 40wt.% 6H silicon carbide powder were mixed, and 5wt.% phenolic resin was added; wet mixing was first performed at a speed of 180r / min for 4h, and then dry mixing was performed at a speed of 100r / min for 5h;
[0098] The second step is to press the powder into shape by a compression molding method, fill the powder into the mold evenly, apply bidirectional pressure at a pressure of 60 MPa, and hold the pressure for 60 seconds; the porosity of the green body is controlled to be 55%.
[0099] The third step is to place the green body molded in the second step on the flat silicon-titanium alloy powder. The silicon-titanium alloy powder adopts the composition of 37Ti63Si and is placed in a vacuum furnace for sintering. The heating rate is 5°C / min, and the temperature is increased to 1650°C, and the temperature is kept for 100 minutes. The vacuum degree is 40pa.
[0100] The fourth step is to heat treat the silicon carbide / titanium silicon carbon composite material product obtained in the third step at a heat treatment temperature of 1700° C., for 2 hours, and at a vacuum degree of 20 Pa.
[0101] In the fifth step, the silicon carbide / titanium silicon carbon composite material product obtained in the fourth step is polished, and the residual silicon on the surface of the sample is treated by sand blasting, and the sand blasting pressure is 0.6 MPa.
[0102] The density of the silicon carbide / titanium silicon carbon composite material in this embodiment is 3.65 g / cm 3 The obtained silicon carbide product has a flexural strength of 550MPa at room temperature, a flexural strength of 350MPa at 1000℃, and a fracture toughness of 5.3MPa·m 1 / 2 .
[0103] Example 10
[0104] This embodiment adopts a reaction sintering method to prepare the 88SiC-12Ti3SiC2 composite material, which specifically includes the following steps:
[0105] In the first step, 40wt.% of nano carbon black and 60wt.% of 6H silicon carbide powder were mixed respectively; the mixture was wet-mixed for 4h using a planetary ball mill at a speed of 200r / min, and after drying, the mixture was dry-mixed for 3h using a planetary ball mill at a speed of 120r / min;
[0106] In the second step, a ceramic slurry is prepared by mixing ceramic powder with a dispersant binder and water, the slurry is poured into a mold made of porous gypsum, the slurry solidifies into a gel by reacting with acrylamide, the gel is removed from the mold and dried to remove excess moisture and shrinkage; the green body porosity is ensured to be 55%;
[0107] The third step is to place the green body prepared in the second step on the flat silicon-titanium alloy powder, and put the silicon-titanium alloy powder with a composition of 37Ti63Si into a vacuum furnace for sintering at a heating rate of 5°C / min to 1700°C and keep the temperature for 150min.
[0108] The fourth step is to heat treat the silicon carbide / titanium silicon carbon composite material obtained in the third step at a heat treatment temperature of 1750°C, for 2 hours, and at a vacuum degree of 20Pa;
[0109] In the fifth step, the silicon carbide / titanium silicon carbon composite material product obtained in the fourth step is polished, and the residual silicon on the surface of the sample is treated by sand blasting, and the sand blasting pressure is 0.6 MPa.
[0110] The density of the silicon carbide / titanium silicon carbon composite material in this embodiment is 3.85 g / cm 3 The obtained silicon carbide / titanium silicon carbon composite material has a flexural strength of 450MPa at room temperature, a flexural strength of 350MPa at 1000℃, and a fracture toughness of 6.5MPa·m 1 / 2 .
Claims
1. A method for preparing a high-purity silicon carbide / titanium silicon-carbon composite material product, characterized in that: The specific steps include: A green body is prepared by using a carbon source and silicon carbide powder, wherein the green body has a porosity of 25% to 55%; the mass fraction of the carbon source in the green body is 10wt.% to 90wt.%, and the rest is silicon carbide powder; The green body is placed on the flat silicon-titanium alloy powder, and heated under vacuum conditions until the silicon-titanium alloy powder melts into liquid and penetrates into the green body, so that the carbon reacts with the silicon-titanium alloy to obtain a silicon carbide / titanium silicon-carbon product; The obtained silicon carbide / titanium silicon carbon product is subjected to high temperature heat treatment to allow the residual silicon-titanium alloy and carbon to fully react, and the silicon carbide / titanium silicon carbon product after high temperature heat treatment is polished to obtain a high-purity silicon carbide / titanium silicon carbon composite material product; The particle size of the silicon carbide powder used is in the range of 0.5 to 50 μm, and the crystal form is 6H or 3C; the carbon source is nano carbon black, mesophase carbon microspheres, artificial graphite, natural graphite, diamond, activated carbon or petroleum coke, and the specifications used are as follows: The particle size of nano carbon black is less than 500nm; the particle size of mesophase carbon microspheres is 2-20μm; the particle size of artificial graphite is 2-20μm; the particle size of natural graphite is 2-20μm; the particle size of diamond is 0.2-50μm; the particle size of petroleum coke is 2-70μm; The green body is placed on the flat silicon-titanium alloy powder, and heated under vacuum conditions until the silicon-titanium alloy powder melts into liquid and penetrates into the green body, so that carbon reacts with the silicon-titanium alloy to obtain silicon carbide / titanium silicon-carbon products. The heating temperature is 1600°C to 1700°C, the holding time is 30 to 180 minutes, and the vacuum degree is not greater than 50Pa; The heat treatment temperature of the obtained silicon carbide / titanium silicon carbon product is 1600°C to 1800°C, the holding time is 2h, and the vacuum degree is 20Pa; The composition range of silicon-titanium alloy powder is 25Ti75Si~50Ti50Si, and the particle size is 0.2-5mm.
2. The method for preparing a high-purity silicon carbide / titanium silicon carbon composite material product according to claim 1, characterized in that: The method of preparing a green body using a carbon source and silicon carbide powder includes: The carbon source and silicon carbide powder are wet mixed and ball milled, and then dried and sieved through a 150-mesh sieve, and the sieved powder is added with phenolic resin or PVA to obtain a wet mixture, and the wet mixture is dried and then dry mixed to obtain a uniformly mixed carbon source and silicon carbide powder; Forming the green body using compression molding, gel casting or extrusion; When using the molding method, the carbon source, silicon carbide powder and binder are mixed evenly, and then molded to obtain a green body; Alternatively, when using gel casting molding, a uniformly mixed carbon source is mixed with silicon carbide powder, a dispersant binder and water to prepare a ceramic slurry, the slurry is poured into a porous gypsum mold, and the ceramic slurry is solidified into a gel state by reacting with acrylamide or agarose, and the gel is taken out and dried to remove excess water and shrinkage to obtain a green body; Alternatively, when the extrusion method is used for molding, the uniformly mixed raw materials are molded, a set amount of water is added to the powder, and a green body is molded by extrusion molding to obtain a green body.
3. The method for preparing a high-purity silicon carbide / titanium silicon carbon composite material product according to claim 2, characterized in that: A planetary ball mill is used for wet mixing, the speed of the planetary ball mill is 180r / min~200r / min, and the powder is mixed for 4 hours. A planetary ball mill is used for dry mixing, the speed of the planetary ball mill is 100r / min~120r / min, and the powder is mixed for 5 hours.
4. The method for preparing a high-purity silicon carbide / titanium silicon carbon composite material product according to claim 2, characterized in that: When preparing green bodies with carbon sources and silicon carbide powder, different molding methods are selected according to the use requirements of different workpieces: for structural parts, compression molding or isostatic pressing is used; for porous parts, grouting molding is used; for pipes, injection molding or extrusion molding is used.
5. A high-purity silicon carbide / titanium silicon carbon composite material product, characterized in that: The high-purity silicon carbide / titanium silicon-carbon composite material product is obtained by the preparation method of any one of claims 1 to 4, and the density of the obtained silicon carbide / titanium silicon-carbon composite material product is 3.46g / cm 3 ~3.90g / cm 3 The volume fraction of residual silicon-titanium alloy in the obtained silicon carbide product is not more than 5 vol.%, the content of Ti3SiC2 in the obtained silicon carbide / titanium silicon-carbon composite material is 15 vol.%-58 vol.%, and the rest is SiC phase; the obtained silicon carbide / titanium silicon-carbon composite material product has a flexural strength of 450MPa-580MPa at room temperature, a flexural strength of 320MPa-370MPa at 1000°C, and a fracture toughness of 4.6-6.5MPa·m 1 / 2 .